'I'm not your mother!': maternal ambivalence and the female investigator in contemporary crime television. Issue 3 (3rd July 2017) - Greer, Amanda
Abstract: Contemporary crime television in the early twenty-first century demonstrates a fixation with maternal identities relating to professional, working women. Its writers, their protagonists and supporting characters,  have become obsessed with maternal ambivalence, specifically,  conflicting feelings of love and hate that mothers feel toward their children. Since motherhood is not simply an unquestionable part of female identity, but an institution naturalized through dominant patriarchal structures, the female investigator figure in crime TV is a particularly rich subject in the exploration of maternal ambivalence and how it plays out in crime TV representation of motherhood. Close examination of  Broadchurch, Happy Valley,  and  The Fall,  featuring strong maternal (or staunchly non-maternal) figures, demonstrates the professional-domestic conflation in the female investigator figure,  using several maternal character tropes (e.g. grieving mother,  Mama Bear),  to effectively explore, stabilize, and even vilify maternal ambivalence. While certain programs condemn the professional woman as a neglectful mother, others allow for a more nuanced exploration of maternal ambivalence, treating maternal identity as a complex and imposing abstraction. These programs' exploration of the female investigator suggests what it means to mother in a world where women are expected to juggle and navigate between numerous identities with ease and grace.